Studi adsorpsi limbah organik industri tahu tempe dengan karbon aktif kayu merbau [Intsia bijuga (Colebr) O. Kuntze] - Noor Endah Setyaningrum; Bimo Budi Santoso; Bertha Mangallo (Program Pascasarjana Universitas Papua, 2019)
Study on adsorption of tofu and tempe industrial organic waste with timber wood [Intsia bijuga (Colebr) O. Kuntze] as the active carbon has been executed. The objective the research is to determine the optimum required consentration of HCl to active the coal of timber wood, discover optimum adsorption capacity of timber charcoal to reduce the level of BOD5 dan COD in fluids waste of tofu and tempe industry. Research method of activating timber wood charcoal is physically by heating 700oC of temperature and chemically by submersion in HCl 1M, 2M and 3M. First, variation is made of contact duration of timber wood active carbon and fluid waste for 30, 60, 90 and 120 minutes. Then, volume of fluid waste is also differed by 100, 150, 200, 250 and 300 ml per 0.5 gram of active carbon. Result of the research shows that optimum condition for adsorption of tofu and tempe industrial fluid waste are as follow : at consentrate of HCl 3M, contact duration 30 minutes, fluid waste volume 250 ml per 0.5 gram of active carbon, optimum adsorption capacity of timber wood active carbon is achieved which lowering the level of BOD5 and COD of Rizky tofu and tempe industrial fluid waste; each by 60,600 mg/g and 12,500 mg/g. On the state where volume of the waste is 100 ml per 0.5 gram, optimum adsorption capacity of the timber wood active carbon in reducing the BOD5 and COD level of Sukamaju tofu and tempe industrial fluid waste is 82,400 mg/g and 164,200 mg/g each.